Rumen Ciliate Fauna of Domestic Sheep (Ovis aries) in İzmir, Turkey and Scanning Electron Microscopic Observations - GÜRELLİ, GÖZDE (Magnolia Press, 2017)
Species composition and distribution of ciliates were investigated in the rumen contents of 15 domestic sheep (Ovis aries) living in İzmir, Turkey. Twenty-three species and 11 morphotypes belonging to nine genera were identified. The density of ciliates was 118.3 ± 63.5 × 104 cells ml−1, and the mean number of ciliate species per host was 13.5 ± 5.3. Entodinium simulans was the most abundant species, with a prevalence of 100%. Two morphotypes of Diplodinium flabellum were identified, such as D. flabellum m. aspinatum and D. flabellum m. monospinatum, and E. simulans m. dubardi was found for the first time in domestic sheep in Turkey. The scanning electron microscopic observations of Entodinium longinucleatum, E. bursa, E. rectangulatum m. rectangulatum, E. semahatae, E. exiguum, E. minimum, E. simulans m. caudatum, E. dilobum, Diplodinium flabellum m. aspinatum, D. dentatum, Isotricha prostoma, Metadinium affine, Enoploplastrom triloricatum, Dasytricha ruminantium, Ophryoscolex caudatus m. tricoronatus, Epidinium ecaudatum m. parvicaudatum, and Polyplastron multivesiculatum were studied.
Keywords: 3. Good health